2021
DOI: 10.1186/s12885-021-08789-2
|View full text |Cite
|
Sign up to set email alerts
|

The value of complete blood count for the prognosis analysis of preoperative esophageal squamous cell carcinoma

Abstract: Objective To investigate the predictive value of preoperative complete blood count for the survival of patients with esophageal squamous cell carcinoma. Methods A total of 1587 patients with pathologically confirmed esophageal squamous cell carcinoma who underwent esophagectomy in the Cancer Hospital Affiliated to Xinjiang Medical University from January 2010 to December 2019 were collected by retrospective study. A total of 359 patients were as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…However, according to the results, the cutoff values obtained by the two methods were not exactly the same. Nevertheless, to date, there are no clear cutoff values for determining the prognosis of EC patients [38]. Therefore, in the future, we plan to explore the best cutoff values and the underlying molecular mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…However, according to the results, the cutoff values obtained by the two methods were not exactly the same. Nevertheless, to date, there are no clear cutoff values for determining the prognosis of EC patients [38]. Therefore, in the future, we plan to explore the best cutoff values and the underlying molecular mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely studied as a predictor or prognostic factor for advanced cancers, including ESCC, gastric cancer, ovarian cancer, and oral cancer ( 25 28 ). With regard to defining the threshold for elevated LMR, previous studies applied critical values from 2.95 to 4 in patients with EC ( 25 , 29 , 30 ). Similarly, we defined the threshold for PLR elevation as 3.26, which is consistent with the threshold of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study also found that high NLR (> 2.20) and PLR (> 110) were associated with larger tumor size, and that NLR was a prognostic factor for resectable ESCC 23 . Another retrospective study of 1587 ESCC patients who underwent esophagectomy found that a high pre-operative NLR (> 3.29) and low LMR (< 2.95) could predict worse survival in patients with ESCC 24 . A recent meta-analysis also confirmed that a high NLR may predict a poor prognosis, including overall survival, cancer-specific survival, and progression-free survival of ESCC patients 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies have reported the roles of NLR/LMR/PLR in patients with advanced-stage esophageal squamous cell carcinoma (ESCC) or in those who received chemoradiation therapy 21 24 , however studies focusing on superficial esophageal cancer or endoscopic resection are still lacking. Therefore, the aims of this study were to evaluate the associations between NLR, LMR, PLR and SESCC, and identify a non-invasive convenient biomarker for the long-term prognosis of patients with SESCC.…”
Section: Introductionmentioning
confidence: 99%